2008
DOI: 10.1097/mph.0b013e31817eb7ef
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Obstructive Sleep Apnea in Children With Sickle Cell Disease

Abstract: Children with SCD suspicious of SDB may have not only a higher incidence of OSAS, but also more severe nocturnal desaturation and hypercapnia as compared with children with uncomplicated OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 44 publications
(39 reference statements)
1
75
2
4
Order By: Relevance
“…This result reflects the prevalence of OSAS in the general population of children and adolescents with SCA at a referral center. This result differs from that of the study conducted by Kaleyias et al, (3) who applied a questionnaire to 100 children, selected only the 19 most severe cases of suspected SDB to undergo polysomnography and concluded that 53% of the selected children had OSAS. In another study, (1) only 35% of the 20 patients studied were found to have OSAS.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This result reflects the prevalence of OSAS in the general population of children and adolescents with SCA at a referral center. This result differs from that of the study conducted by Kaleyias et al, (3) who applied a questionnaire to 100 children, selected only the 19 most severe cases of suspected SDB to undergo polysomnography and concluded that 53% of the selected children had OSAS. In another study, (1) only 35% of the 20 patients studied were found to have OSAS.…”
Section: Discussioncontrasting
confidence: 55%
“…Children and adolescents with sleep apnea presented a significantly higher percentage of arousals during sleep. (3) In the present study, the frequency of nocturnal desaturation was increased (81.2%). A similar result was obtained by another group of authors, (3) who carried out a study using polysomnography and capnography.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Obstructive sleep apnea (OSA) is the commonest of these disorders [57]. Few studies have described sleep-disordered breathing and OSA in children and adolescent with SCA using polysomnography(PSG) [23,[58][59][60][61][62]. OSA was reported in 10-80% of children with Sickle cell disease [58][59][60][61][62]23].…”
Section: Ne and Sleep-related Disorders In Scamentioning
confidence: 99%